Charity Project Managment on the Example of the Child Support Plan Project for Children without Parental Care in Jiangxi Province: Implementation Status, Problems and countermeasures - Huang, Hailun (Lesya Ukrainka Volyn National University, 2024)
According to the survey results of the Ministry of Civil Affairs in 2020, there are still more than 6.436 million left-behind children in rural areas facing various problems, and the development of rural children still faces outstanding challenges. It is obviously not enough to rely solely on the government to solve the problems of left-behind children in rural areas. The report of the 19th National Congress pointed out that it is necessary to improve the care and service system for left-behind children in rural areas, and the Fifth Plenary Session of the 19th Central Committee pointed out that charity should play a role in the third distribution. 2021 is the first year of the 14th Five-Year Plan and the long-term goal of 2035, and the country is paying more and more attention to the group of left-behind children in rural areas. China's charity and social work have made great achievements in the field of left-behind children, and relying on the power of social work is an effective way to solve the problem of left-behind children in rural areas. In this paper, taking the care project “Child Companion Plan” of left-behind children in L County, Jiangxi Province as an example, through literature research, interviews, participation observation and other data collection methods, the author investigates and analyzes the operation mode of “Child Companion Plan”, summarizes the implementation status of “Child Companion Plan” in L County, and discusses the application of social work in the operation process of "Child Companion Plan". Judging from the implementation of the project, the “Child Companion Plan” project itself is a systematic operation and management mechanism, which is reflected in the management of the child companion home and the child companion mother. The supporting role of “charity” to the "child companion program" is reflected in the control of the operation and management of the project by the provincial charity association and the China Foundation for Poverty Alleviation and the financial support for the project; The supporting function of “social work” to “child companion program” is embodied in training and supervision, and the application of social work methods. It is found that there are some problems in the implementation of the “Child Companion Program”, such as the lack of professionalism of child companion mothers, the lack of continuous training and supervision due to the epidemic situation, the shortage of funds for the follow-up activities of the project, the low participation of families and communities, and the lack of joint support from all sectors of society. In view of the above problems, this paper puts forward some suggestions for the optimization of the “Child Companion Plan” project: first, we should strengthen the professional construction, on the one hand, children's companion mothers should strengthen their self-professional knowledge learning, charitable organizations should improve their professional service level and the management ability of project managers through training and supervision, on the other hand, relying on local professional social work institutions and universities to build a team of children’s service talents suitable for Jiangxi and improve the corresponding talent mechanism; Second, it is necessary to improve the financial support for the project and raise the professional level of fundraising for the project; Third, advocate the participation of family and community, improve the participation of guardians, expand the participation methods of guardians, and give full play to the participation subjectivity of guardians and communities; The fourth is to seek multi-party continuous participation and concern, strengthen the linkage support between government groups and organizations for the project, improve the service network construction for leftbehind children, and set up local volunteer teams to let more resources benefit leftbehind children in rural areas of Jiangxi.
Keywords: child companion program; care project for left-behind children; social work; charitable organization